Herding, Warfare, and a Culture of Honor: Global Evidence - Yiming Cao; Benjamin Enke; Armin Falk; Paola Giuliano; Nathan Nunn (Center for Economic Studies and ifo Institute (CESifo), 2022)
According to the widely known 'culture of honor' hypothesis from social psychology, traditional herding practices have generated a value system conducive to revenge-taking and violence. We test the economic significance of this idea at a global scale using a combination of ethnographic and folklore data, global information on conflicts, and multinational surveys. We find that the descendants of herders have significantly more frequent and severe conflict today, and report being more willing to take revenge in global surveys. We conclude that herding practices generated a functional psychology that plays a role in shaping conflict across the globe.
Keywords: 330